Evolutionary explanations of eating disorders - Kardum, Igor (Array, 2008)
Summary: This article reviews several most important evolutionary mechanisms that underlie eating disorders. The first part clarifies evolutionary foundations of mental disorders and various mechanisms leading to their development. In the second part selective pressures and evolved adaptations causing contemporary epidemic of obesity as well as differences in dietary regimes and life-style between modern humans and their ancestors are described. Concerning eating disorders, a number of current evolutionary explanations of anorexia nervosa are presented together with their main weaknesses. Evolutionary explanations of eating disorders based on the reproductive suppression hypothesis and its variants derived from kin selection theory and the model of parental manipulation were elaborated. The sexual competition hypothesis of eating disorder, adapted to flee famine hypothesis as well as explanation based on the concept of social attention holding power and the need to belonging were also explained. The importance of evolutionary theory in modern conceptualization and research of eating disorders is emphasized